Cultural Diversity and Harmony of Tionghoa Good Character: Towards Unity with Incremental Change of Citizenship - Nufus , Achmad Busrotun; Malihah, Elly; Darmawan, Cecep; Anggraeni, Leni; Budimansyah, Dasim; Sehadun, Fransiskus (Universitas PGRI Kanjuruhan Malang, 2024)
Indonesia, as a country with rich cultural diversity, shows a strong commitment to developing social dynamics to care for and maintain this diversity. This research explores the role of ethnic Tionghoa in their contribution to national diversity and unity. Through qualitative methods with an ethnographic approach and literature study, with a total of 30 ethnic Tionghoa informants, this research found that the values ​​of tolerance, respect for differences and mutual cooperation implemented by the Tionghoa community play an important role in maintaining social harmony in Indonesia. Research results have shown that Indonesian people, including ethnic Tionghoa, view cultural diversity as a wealth that enriches national identity and strengthens national unity. Ethnic Tionghoa actively participate in preserving and advancing their cultural traditions, as well as demonstrating the values ​​of tolerance, respect for differences and mutual cooperation in everyday life. These values ​​have proven effective in maintaining social harmony and overcoming potential inter-ethnic conflicts. In addition, the policy of incremental change in citizenship has helped integrate various ethnic groups, including ethnic Tionghoa, within an inclusive national framework, thereby strengthening national unity gradually and sustainably.